Aminopeptidase A, which generates one of the main effector peptides of the brain renin-angiotensin system, angiotensin III, has a key role in central control of arterial blood pressure. (August 2000) - Reaux, A.; Iturrioz, X.; Vazeux, G.; Fournie-Zaluski, M.-C.; David, C.; Roques, B. P.; Corvol, P.; Llorens-Cortes, C.
Abstract : Overactivity of the brain renin-angiotensin system (RAS) has been implicated in the development and maintenance of hypertension in several experimental animal models. We have recently reported that, in the murine brain RAS, angiotensin II (AngII) is converted by aminopeptidase A (APA) into angiotensin III (AngIII), which is itself degraded by aminopeptidase N (APN), both peptides being equipotent to increase vasopressin release and arterial blood pressure when injected by the intracerebroventricular (i.c.v.) route. Because AngII is converted in vivo into AngIII, the exact nature of the active peptide is not precisely known. To delineate their respective roles in the central control of cardiovascular functions, specific and selective APA and APN inhibitors are needed to block the metabolic pathways of AngII and AngIII respectively. In the absence of such compounds for APA, we first explored the organization of the APA active site by site-directed mutagenesis. This led us to propose a molecular mechanism of action for APA similar to that proposed for the bacterial enzyme thermolysin deduced from X-ray diffraction studies. Secondly, we developed a specific and selective APA inhibitor, compound EC33 [( S )-3-amino-4-mercaptobutylsulphonic acid], as well as a potent and selective APN inhibitor, PC18 (2-amino-4-methylsulphonylbutane thiol). With these new tools we examined the respective roles of AngII and AngIII in the central control of arterial blood pressure. A central blockade of APA with the APA inhibitor EC33 suppressed the pressor effect of exogenous AngII, suggesting that brain AngII must be converted into AngIII to increase arterial blood pressure. Furthermore, EC33, injected alone i.c.v. but not intravenously, caused a dose-dependent decrease in arterial blood pressure by blocking the formation of brain AngIII but not systemic AngIII. This is corroborated by the fact that the selective APN inhibitor PC 18 administered alone via the i.c.v. route increased arterial blood pressure. This pressor response was blocked by prior treatment with the angiotensin type 1 receptor antagonist losartan, showing that blocking the action of APN on AngIII metabolism leads to an increase in endogenous AngIII levels, resulting in arterial blood pressure increase through an interaction with angiotensin type 1 receptors. These results demonstrate that AngIII is a major effector peptide of the brain RAS, exerting a tonic stimulatory control over arterial blood pressure. Thus APA, the enzyme responsible for the formation of brain AngIII, represents a potential central therapeutic target that justifies the development of APA inhibitors, crossing the blood-brain barrier, as central anti-hypertensive agents.